The Common Follicle-Stimulating Hormone Receptor (FSHR) Promoter Polymorphism FSHR −29G > A Affects Androgen Production in Normal Human Small Antral Follicles - Borgbo, Tanni; Klučková, Hana; Macek, Milan; Chrudimska, Jana; Kristensen, Stine Gry; Hansen, Lise Lotte; Andersen, Claus Yding (Frontiers in Endocrinology, 2017)
Follicle-stimulating hormone receptors (FSHRs) are almost exclusively expressed on granulosa cells, and FSH action is probably most clearly reflected in intrafollicular hormone milieu of antral follicles. Little is known about the possible effects of the common single nucleotide polymorphism (SNP) FSHR −29G > A (rs1394205) on hormonal conditions in humsan small antral follicles (hSAFs) obtained from women in the natural menstrual cycle. This study investigated the follicle fluid (FF) concentrations of anti-Müllerian hormone, estradiol, progesterone, androstenedione, and testosterone in hSAF in relation to the different genotypes of FSHR −29G > A. FF from 362 follicles was collected in 95 women undergoing fertility preservation, who did not suffer from a disease that directly affected ovarian function. The testosterone levels of the minor A/A genotype were significantly increased compared to the A/G and the G/G genotype. Furthermore, significantly reduced androstenedione levels were observed for the G/G genotype, as compared to the A/G genotype, while the other hormones did not show statistical significant differences. In conclusion, the androgen levels of hSAF were significantly elevated in the minor SNP genotype in the FSHR promoter polymorphism FSHR −29G > A.